IMPLEMENTASI BAURAN PROMOSI DI STIA MALANG - Marhaeni, Tri; Kristanto, Dadang; Adiba, Farah (STIA MALANG, 2025)
This study aims to analyze the promotional mix implemented by STIA Malang in facing intense competition among universities in East Java. Using a descriptive qualitative approach, data was obtained through in-depth interviews and direct observation of campus promotional activities. STIA Malang utilizes various promotional media such as brochures, banners, billboards, radio advertisements, social media (Instagram and TikTok), as well as direct marketing via SMS and WhatsApp blasts, and school visits. The results indicate that the combination of conventional and digital media can increase campus visibility and attract prospective new students. These findings are reinforced by the application of the marketing mix theory (4Ps) and the promotional mix as a conceptual framework. This study recommends increasing the integration of digital marketing for optimal promotional effectiveness.